Las retahílas en el desarrollo del lenguaje en los niños de primer año de educación básica de la escuela de educación básica San Felipe Neri de la parroquia Lizarzaburu, Cantón Riobamba, Provincia de Chimborazo, periodo octubre 2020- marzo 2021 - Paca Espinoza, María Jenny (2021)
The present investigative work tries to establish the importance of the strings in the oral language of the children of the first year of basic education of the San Felipe Neri school, the general objective was to develop the language through the use of the strings, the specific objectives were ; Analyze the level of language development, identify the different types of strings and demonstrate that the methodological strategies used by the teacher develop language in children in the first year of Basic Education, a theoretical framework was made to know the authors' criteria on the object of study, the methodology used was field and bibliographic, with 30 children and 3 teachers, the results determine that the level of language development of children is low, a large percentage of children have difficulties memorizing, pronouncing, analyzing , retain and discriminate the information received, a pictographic story was used to assess expression, fluency, understanding, coherence and discrimination. The main conclusion was; the level of language development in the children of the "San Felipe Neri" Basic Education School is not adequate. 61% of the children have difficulties memorizing, pronouncing, analyzing, retaining and discriminating the information received.